The Intersection of Human Rights and Bioethics in International Law (A Comparative Study of Genetic Technology Regulation in the Asean Region - Wagiman Martedjo; Lisno Setiawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study explores the relationship between Human Rights (HAM), bioethical principles, and the international legal framework in responding to the rapid development of genetic technology. The background of this study is based on the legal vacuum and ethical dilemmas related to genetic editing, cloning, and DNA manipulation that have the potential to violate human dignity and the right to genetic integrity. The main problem arises when scientific innovation exceeds the speed of legal regulation, thus triggering the risk of genetic discrimination and the commodification of life. The formulation of the problem in this study is: (1) How are bioethical principles integrated into international human rights instruments to regulate genetic technology? and (2) How do the legal policies of ASEAN countries compare in protecting their citizens from the misuse of genetic technology? The research method used is normative juridical using a conceptual approach to examine bioethical theory, a legislative approach to international instruments such as the Universal Declaration on Bioethics and Human Rights, and a comparative approach in the ASEAN region (particularly a comparison between Indonesia, Singapore, and Thailand). The results of the study indicate that although international instruments have laid the foundation for protecting human dignity, implementation at the ASEAN regional level is still very fragmented. Singapore has highly permissive regulations for biomedical advancement, while other countries still rely on general ethical norms without a strong legal framework. In conclusion, harmonization of scientific progress and the protection of fundamental rights is necessary to prevent genetic technology from harming humanity. Suggestions include the establishment of legally binding ASEAN regional bioethics guidelines and the strengthening of domestic legislation that specifically prohibits genetic discrimination.